Just Friends? Managers’ Connections to Judges - HUANG, STERLING; ROYCHOWDHURY, SUGATA; SLETTEN, EWA; XU, YANPING (Journal of Accounting Research, 2025)
ABSTRACT We study the impact of social connections between judges and executives on the outcomes of Securities Class Action Litigation (SCAL). Judges who are socially connected to a firm's executives are significantly more likely to dismiss lawsuits against the firm. There is also evidence of faster resolution and lower payout amounts in connected cases. The favorable outcomes cannot be explained by the lower severity of connected cases, or by court, judge, or firm characteristics. Our results are more pronounced when executives connected to the judge are named defendants in the lawsuits, when connected cases involve less visible lawsuits or firms, and when connections between judges and executives are likely more direct. Our evidence indicates that social connections influence judge impartiality and meaningfully alter SCAL outcomes.